INVESTIGATION OF THE EFFECT OF CARBONATION CAKE ON RHEOLOGICAL PROPERTIES OF BITUMINOUS BINDERS - Özdemir, Ahmet Münir; Yalçın, Erkut; Arslanoğlu, Hasan; Yilmaz, Mehmet; Kök, Baha (Necip Fazıl YILMAZ, 2021)
Aggregates and bitumen used in road flexible pavements are non-renewable natural materials and in terms of sustainability, it is of great importance that the service life of road pavements is long. Waste materials are also rising with increasing products due to industrial development. The evaluation of waste materials both prevents the destruction of nature by reducing the use of very limited natural materials and reduces the environmental problems in case of storage of waste materials. In this study, carbonation cake, which is a waste of sugar factory, was added to bitumen. Penetration, softening point, rotational viscosity and dynamic shear rheometer tests were applied on pure and modified bitumen. According to the results, it was determined that carbonation cake had no positive or negative effect on medium and high temperature rheological properties of bitumen. From the experiments, promising results have been obtained for the disposal of waste carbonation cake in a different area.
Keywords: Engineering; Mühendislik; Material Production Technologies; Malzeme Üretim Teknolojileri